Spatial-Temporal Evolution of the Gas Hydrate Stability Zone and Accumulation Patterns of Double BSRs Formation in the Shenhu Area - Song, Yingrui; Lei, Yuhong; Zhang, Likuan; Cheng, Ming; Li, Chao; Liu, Naigui (Frontiers in Earth Science, 2022)
The current study examines the methane gas hydrate stability zone (GHSZ) in the Shenhu area in the northern South China Sea (SCS) as an example to calculate the thickness of the GHSZ and reconstruct its evolution since 8.2 Ma. Two mechanisms for typical double BSRs in the Shenhu area are shown, and the relationship between the evolving thickness of the GHSZ and the dynamic accumulation of NGHs at typical stations in the Shenhu area is clarified. The results show that the thickness of the GHSZ varies over time with overall thickening in the Shenhu area. The current thickness of the GHSZ is between 160.98 and 267.94 m. Two mechanisms of double BSRs in the Shenhu area are summarized: the double BSRs pattern based on changes in formation temperature, pressure and other conditions and the double BSRs pattern based on differences in gas source and composition. The formation process and occurrence characteristics of double BSRs and hydrate at site SH-W07-2016 in the Shenhu area are also closely related to the changes in thickness of the GHSZ. In addition, the age when gas source first enters the GHSZ has a considerable influence on the dynamic accumulation process of hydrate. Since the formation of hydrate above the BSR at site SH-W07-2016, the GHSZ has experienced up to two periods of thickening and two periods of thinning at this site. With the changes in the thickness of the GHSZ, up to two stages of hydrate formation and at most two stages of hydrate decomposition have occurred. This paper is of great value for understanding the formation of multiple bottom-simulating reflectors (BSRs) as well as the migration, accumulation and dissipation of natural gas hydrate (NGH) during the dynamic accumulation process.